Numerical modelling of the developed horizontal circulation in the atmospheric boundary layer - Ponomarev, Vasily Mikhailovich; Ckhetiani, Otto Guramovich; Shestakova, Lidia Valentinovna (Computational Continuum Mechanics, 2009)
A numerical model taking into account the turbulent helicity effect has been developed to describe the dynamics of organized vortex structures in the Ekman atmospheric boundary layer. The numerical results indicate that the vortices have the sizes and periodicity close to those observed experimentally. The obtained results are found to be consistent with the theoretical predictions for the helicity effect on direct energy cascade weakening toward small-scale modes.